Applied Design Research A Mosaic of 22 Examples, Experiences and Interpretations Focussing on Bridging the Gap between Practice and Academics - Joore, Peter; Stompff, Guido; van den Eijnde, Jeroen (Taylor & Francis, 2022)
Design and research are two fields of knowledge that each has its traditions, methods, standards and practices. These two worlds appear to be quite separate, with researchers investigating what exists, and designers visualising what could be. This book builds a bridge between both worlds by showing how design and research can be integrated to develop a new field of knowledge. Applied Design Research: A Mosaic of 22 Examples, Experiences and Interpretations Focussing on Bridging the Gap between Practice and Academics contains 22 inspiring reflections that demonstrate how the unique qualities of research (aimed at studdying the present) and design (aimed at developing the future) can be combined. This book shows that the transdisciplinary approach is applicable in a multitude of sectors, ranging from healthcare, urban planning, circular economy, and the food industry. Arranged in five parts, the book offers a range of illustrative examples, experiences, methods, and interpretations. Together they make up the characteristic of a mosaic, each piece contributing a part of the complete picture, and all pieces together offering a multi-facted perspective of what applied design research is, how it is implemented and what the reader can expect from it. This book with its bearings in practice can enthuse early-stage researchers with the diversity of its examples, while more senior design researchers may recognize themselves in the depth of the experiences described and be inspired by them. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.